E-Health - A Strategy to Increase Quality in Health Care in Europe And in Romania - Laura Agata TOC-BIVOL (Communications of International Proceedings, 2021)
We are confronting in the past years with an increase in the need of digital medical services, in part because of the aim to create easier links between citizens and medical staff, part from economical reasons. Each country has its regulation and for easier access to all people, European countries try to find legal ways for the safe access to medical records for people, but for medical staff also. The legal framework is under continuous implementation and correction in order to maintain and increase the quality of the health care system. Each country has its own regulation and European Commission has its own agenda regarding digital health. The COVID-19 pandemic showed the need for digital services in all areas and in all countries around the globe and accelerated the digital transformation especially in the medical field, but in other sectors also. In the paper below we analyzed a number of 15 sources, to show changes in the past years in Romania regarding e-Health, legal framework, steps for implementation, the importance of digitizing the activity of the medical staff, telemedicine, access to personal records, access to internet in order to find the suitable health care, even from distance.
Keywords: Health Care System; Digital; Quality of Medical Services; E-Health.